Climate-induced Gender Vulnerabilities in Northwestern Bangladesh. (October 2017) - Tanny, Nishith Zahan; Rahman, M. Wakilur; Ali, Rafiqun Nessa
Risks and vulnerabilities arising out of climate change are exacerbated by unequal gender relations. The current study examines climate-induced vulnerabilities to which men and women are exposed and explores the factors that affect women more than men. This study was conducted in purposively selected Kurigram district as a representative of Northern Bangladesh, where people experience climatic divergence and extreme poverty. Data were collected from 100 randomly selected participants from three villages of Kurigram district through questionnaire survey and focus group discussions. The gender vulnerability index was used to measure the extent of vulnerability and the factors influencing vulnerability. The results show that 72.2 per cent are highly vulnerable with females being almost more than twice as vulnerable as males. The analysis indicates that the amount of land, difficulty in bathing when the basic bathroom structure was destroyed and use of borrowed money were the main determinants of gender vulnerability in changing climatic conditions. The findings of this study might help to integrate gender into climate change policy discourse and find appropriate adaptation strategies in Bangladesh, particularly in Northwestern Bangladesh.